The essentials of mathematics, grades 7-12 : effective curriculum, instruction, and assessment - Checkley, Kathy (Priorities in practice., 2006)
"One of the biggest challenges facing math educators today is preparing students for the unknown. How much math knowledge is enough for students who must be ready to contribute to industries yet born through technologies yet created? Although the "how much" question still inspires debate, educators agree that failing to improve mathematics instruction threatens too many students' futures." "In this book, therefore, award-winning mathematics teachers and respected math researchers share their perspectives on how to best improve the mathematics education all students receive. Teachers show how they are striving for equity. The stakes are high and every student needs to attain a higher level of mathematics understanding. The exemplary educators featured in this book share some proven strategies for helping them do so. Teachers share innovative lessons that address standards and help students see how math can be used in the world. Education experts discuss the research that influences how curriculum is developed and how instructional choices are made. Teachers and educators explore ways to vary instruction to meet their students' unique learning needs. Professional development experts, including teachers, discuss the kinds of learning experiences that teachers want and need. We hope the ideas and perspectives you read about this book will inspire you and aid you in helping students achieve a profound understanding of mathematical concepts. Book jacket."--Jacket.